2023
DOI: 10.1021/acssynbio.3c00241
|View full text |Cite
|
Sign up to set email alerts
|

A Layered Genetic Design Enables the Yeast Galactose Regulon to Respond to Cyanamide

Jingya Song,
Jian Fan,
Cong Fan
et al.

Abstract: The commonly used expression systems in Saccharomyces cerevisiae typically rely on either constitutive or galactose-regulated promoters. The lack of inducible systems in S. cerevisiae limits the precise temporal regulation of protein function and yeast metabolism. We herein repurposed the galactose-regulated system to make it respond to cyanamide. By using a cyanamide-inducible DDI2 promoter to control Gal4 expression in CEN.PK2−1C with Δgal80, a tight and graded cyanamide-inducible GAL system with an enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…2 C), we constructed a 2μ plasmid containing the gene expression cassette of eGFP-2A-PEST-CUP1 and transformed it into JY-Cyan-∆cup1. Since the cyanamide-inducible GAL system is tightly regulated by cyanamide [ 26 ], we observed that the engineered strain exhibited viability only when the cyanamide inducer was added to trigger the expression of eGFP-2A-PEST-CUP1 (Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 C), we constructed a 2μ plasmid containing the gene expression cassette of eGFP-2A-PEST-CUP1 and transformed it into JY-Cyan-∆cup1. Since the cyanamide-inducible GAL system is tightly regulated by cyanamide [ 26 ], we observed that the engineered strain exhibited viability only when the cyanamide inducer was added to trigger the expression of eGFP-2A-PEST-CUP1 (Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Upon the construction of copper-susceptible S. cerevisiae and the validation of functional expression of the 2A-PEST-CUP1 module, we subsequently aimed to investigate whether the gene expression cassette could be integrated at the δ sites by applying the copper selection [ 29 , 39 ]. Since the ability of yeast strains to resist Cu 2+ was affected not only by the number of integrated copies but also by the expression level of CUP1 gene, we adopted our recently constructed cyanamide-inducible GAL system [ 26 ], so that the gene expression cassette can be tightly regulated by cyanamide concentrations. This approach ensures that even a low amount of inducer could lead to much higher selection pressure for multi-integration events.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains with α-factor under glucose-repressible promoters were integrated with the P GAL1 -EGFP expression cassette at the gal7-10-1 locus. 59 14 mL sterile tubes containing 2 mL YPD medium were inoculated with fresh overnight cultures to an initial OD 600 of 0.1. The cell cultures were incubated at 30°C and 200 rpm, and 100 μL of cell culture in YPD were collected by centrifugation at 3000 g and resuspended with equal volume water before measuring OD 600 and green fluorescence intensities.…”
Section: Methodsmentioning
confidence: 99%